xy+x+y=11; {xy+x+y=11;
{x²y+xy²=30. ⇒ {xy(x+y)=30.
Пусть х+у=u; xy=v
{v+u=11;
{vu=30.
Решаем систему подстановки:
{v=11-u;
{(11-u)u=30.
Решаем второе уравнение системы
u²-11u+30=0
D=(-11)²-4·30=121-120=1
u₁=(11-1)/2=5 или u₂=(11+1)/2=6
v₁=11-u₁=11-5=6 или v₂=11-6=5
Обратная замена
{x+y=5 или {x+y=6
{xy=6 {xy=5
{y=5-x {y=6-x
{x(5-x)=6 {x(6-x)=5
Решаем вторые уравнения систем:
x²-5x+6=0 x²-6x+5=0
D=25-24=1 D=36-20=16
x₁=(5-1)/2=2; x₂=(5+1)/2=3 x₃=(6-4)/2=1; x₄=(6+4)/2=5
y₁=5-2=3; y₂=5-3=2 y₃=6-1=5; y₄=6-5=1
О т в е т. (2;3) (3;2) (1;5) (5;1).
ответ: 1,6
Объяснение:
1)![\frac{1}{t-2}-\frac{6}{t+2}=\frac{1}{t-2}\cdot\frac{6}{t+2}\\\frac{t+2-6(t-2)}{(t-2)(t+2)} =\frac{6}{(t-2)(t+2)} \\t+2-6t+12=6\\-5t=6-14\\-5t=-8\\t=8/5\\t=1,6](/tpl/images/1048/1615/a974b.png)
2)![\frac{8t+19}{8t+1}=\frac{8t-1}{8t}\\8t(8t+19)=(8t-1)(8t+1);\\64t^2+152t=64t^2-1,\\152t=-1 \Rightarrow t = -\frac{1}{152}.](/tpl/images/1048/1615/5bc6d.png)